Budget Travel Trends in Yogyakarta From a Backpacker Style Perspective - Moch Nur Syamsu; Agung yuliyanto Nugroho (Nawasena: Jurnal Ilmiah Pariwisata, 2025)
The backpacker tourism trend in Indonesia, especially in Yogyakarta, has grown rapidly in recent years, with Yogyakarta becoming one of the main destinations for tourists with a fairly limited budget. This research aims to identify the factors that make Yogyakarta a favorite destination for backpackers in the region. The research methodology includes literature analysis, interviews with backpackers, and tourism statistics. The results show that the combination of natural beauty, cultural diversity, affordable living costs, good tourism infrastructure, and easy access to various tourist attractions are the main factors that attract backpackers. Apart from that, Yogyakarta's image as a friendly, safe and open area for foreign tourists also contributes to its popularity. This study also compares Yogyakarta with regional regions such as Bandung, Malang and Bali to understand Yogyakarta's competitive advantages. These findings provide insight for the government and tourism industry players in developing sustainable strategies to maintain and increase the attractiveness of destinations for the backpacker tourism segment